PENINGKATAN EKONOMI MASYARAKAT MELALUI PELATIHAN PEMBUATAN JILBAB DENGAN TEKNIK ECOPRINT DAN SHIBORI DI PEDUKUHAN NGENTAK SELOHARJO PUNDONG BANTUL - Alicia Christy Zvereva Gadi; Kusminarko Warno; Enny Zuhni Khayati; Sri Emy Yuli Suprihatin; Widyabakti Sabatari (Institut Seni Indonesia Surakarta, 2024)
Currently, motifs on textiles areincreasingly diverse, but they can still be developed by applying various textile techniques. Multiple innovations in textile techniques have emerged, including coloring techniques and creating motifs by considering environmental sustainability. Ecoprint and Shibori techniques are new opportunities with great potential for people who want to open a textile business but are also environmentally friendly. The aim of this community service activity is: (1) to find a design and manufacture of hijab based on a combination of ecoprint and shibori techniques that is unique, attractive, creative, and currently trending in Ngentak, Seloharjo, Pundong, Bantul; (2) carrying out training in hijabs manufacturing based on a combination of ecoprint and shibori techniques in Ngentak Seloharjo Pundong Bantul; (3) producing hijab products based on a combination of ecoprint and shibori techniques in Ngentak Seloharjo Pundong Bantul that are suitable for sale. The methods used include: (1) the activity methods used in this community service are in the form of lectures, questions and answers, discussions, individual practice, and mentoring; (2) lecture method, question and answer, and discussion to provide knowledge regarding ecoprint and shibori techniques, designs, materials and motif patterns; (3) individual practice method, assistance in making hijabs based on a combination of ecoprint and shibori techniques. The result of the training activities of making hijabs based on a combination of ecoprint and shibori techniques is 20 marketable hijab products with designs combined with ecoprint and shibori techniques from quality natural materials and dyes